Korelasi Al-Qur'an Surah Al Hujurat Ayat 11-13 Dengan Manajemen Pendidikan Islam - Husin, Saddam; Junaidi, Erik; Sa'idah, Nur (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
This research aims to explore the implications of moral education from Surah Al-Hujurat verses 11-13 for the younger generation who tend to lack manners and etiquette. The research method used is a literature study with a content analysis approach, which highlights the concept of moral education through interpretation of the Al-Qur'an. The findings show that the letter emphasizes the importance of respect, not having prejudice, and increasing piety. The implication is the importance of moral education today, where educators have a key role in transferring Islamic values to students, so that through example, advice and habituation, they can form noble morals. Future studies are expected to explore the adaptation of behavior to developments over time, which could provide better insight into responding to the needs of modern Muslim societies.